"Quite indifferent to these things": The Role of Emotions and Conversion in the Dutch East India Company's Interactions with the South Lands. (19th May 2015) - Broomhall, Susan
Abstract : This article situates the engagement of the Dutch East India Company (the Vereenigde Oostindische Compagnie, or VOC) with the South Lands in the context of diverse understandings of the missionary endeavour within the Company in the first half of the seventeenth century. In that light, it argues that both emotions and the idea of evangelising were critical to the objectives and experiences of the VOC in regards to the South Lands. Powerful feelings about evangelising informed both why and how the Company engaged with this region, shaping the nature of discussion within the Company archives about this endeavour. These sentiments were not consistent across the Company but were shaped by a wide range of factors that includes specific social, political, and economic motives for the Company, the hierarchical status of author and readership, the nature and purpose of the compositional form, individual social and confessional identities, professional expertise, and experiences in the region. Moreover, Company men's interpretations of the emotions of local peoples in regards to Company objectives were critical to their judgments about the susceptibility of these people to evangelising and the Company's decisions about its obligations to spread Christian doctrine in the region.